2023
DOI: 10.1002/acn3.51783
|View full text |Cite
|
Sign up to set email alerts
|

Effects of apolipoprotein E polymorphism on cerebral oxygen saturation, cerebral perfusion, and early prognosis after traumatic brain injury

Abstract: Objective To investigate the effects of the apolipoprotein E (APOE) gene on oxygen saturation and cerebral perfusion in the early stages of traumatic brain injury (TBI). Methods This study included 136 consecutive TBI patients and 51 healthy individuals. The APOE genotypes of all subjects were determined using quantitative fluorescence polymerase chain reaction (QF‐PCR). Regional cerebral oxygen saturation (rScO2) of patients with TBI and normal subjects was monitored using near‐infrared spectroscopy (NIRS). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Recent findings link acute and subacute mTBI recovery with another risk factor, the apolipoprotein epsilon 4 (APOE e4) genetic polymorphism. These data revealed that APOE e4 carriers with mTBI had even lower cerebral oxygen saturation [42] and irregular neural slow wave activity [43] and lower perfusion [44] than non-carriers. In short, in mTBI, recovery is complicated by interactions with other risk factors that are only beginning to be understood.…”
Section: Linking Mtbi Sequelae To Dementia Riskmentioning
confidence: 85%
“…Recent findings link acute and subacute mTBI recovery with another risk factor, the apolipoprotein epsilon 4 (APOE e4) genetic polymorphism. These data revealed that APOE e4 carriers with mTBI had even lower cerebral oxygen saturation [42] and irregular neural slow wave activity [43] and lower perfusion [44] than non-carriers. In short, in mTBI, recovery is complicated by interactions with other risk factors that are only beginning to be understood.…”
Section: Linking Mtbi Sequelae To Dementia Riskmentioning
confidence: 85%